PENERAPAN TEORI AKOMODASI DALAM SOSIOLINGUISTIK UNTUK MENGENALI PEMERTAHANAN ATAU PERALIHAN BAHASA DALAM MASYARAKAT PERANTAU - Simanjuntak, Hotma (Jurnal Kajian Pembelajaran dan Keilmuan, 2023)
AbstractOne of emigrant societies in Pontianak and its vicinity is the Batak Toba. It is assumed that there are three generations of them in the area. They originate from north Tapanuli, north Sumatra province. They have existed in Pontianak as a minority among the majority: Malay, Tionghoa, Javanese, Dayaknese, Madurese and Bugisnese. In the beginning they used Batak Toba language as a means of communication with fellow emigrants. They use the Indonesian language to communicate with non-Batak Toba societies in conducting state affair or official duties. Nowadays the Batak Toba language, as used by the three generations, is in the danger of extinction, or experiencing language shift. One of the causes of this phenomenon is language accomodation that digresses from common parlance in various domains. It is expected that the application of the teaching and learning of Sociolinguistics could encourage students to do a research on language maintenance or language shift among the emigrant societies.